2015
DOI: 10.1186/s12958-015-0118-9
|View full text |Cite
|
Sign up to set email alerts
|

Metabolites involved in cellular communication among human cumulus-oocyte-complex and sperm during in vitro fertilization

Abstract: BackgroundFertilization is a key physiological process for the preservation of the species. Consequently, different mechanisms affecting the sperm and the oocyte have been developed to ensure a successful fertilization. Thus, sperm acrosome reaction is necessary for the egg coat penetration and sperm-oolema fusion. Several molecules are able to induce the sperm acrosome reaction; however, this process should be produced coordinately in time and in the space to allow the success of fertilization between gametes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 90 publications
(77 reference statements)
0
7
0
Order By: Relevance
“…A study revealed that the age-related alterations in the lipid metabolite LPC in FF may be related to oocyte quality 38 . In addition, a study examining IVF metabolomics demonstrated that LPC served a paracrine role on oocytes and participates in the acrosomal reaction 39 . Bertevello et al analyzed lipid profiles of LFs and SFs within the same bovine ovaries, and reported that LPC, PC, and a number of non-annotated low-weight lipid species were differentially abundant between the follicles 25 .…”
Section: Discussionmentioning
confidence: 99%
“…A study revealed that the age-related alterations in the lipid metabolite LPC in FF may be related to oocyte quality 38 . In addition, a study examining IVF metabolomics demonstrated that LPC served a paracrine role on oocytes and participates in the acrosomal reaction 39 . Bertevello et al analyzed lipid profiles of LFs and SFs within the same bovine ovaries, and reported that LPC, PC, and a number of non-annotated low-weight lipid species were differentially abundant between the follicles 25 .…”
Section: Discussionmentioning
confidence: 99%
“…We screened three significantly different metabolites that might affect the egg production performance of Taihe black-bone silky fowl: LPC 20:4, Bisphenol A, and Cortisol. LPC 20:4 is an isoform of lysophosphatidylcholine (LPC), and it has been shown that LPC not only affects the acrosome response of sperm and eggs, but also mediates paracrine actions in oocytes ( Gomez-Torres et al, 2015 ). Yang et al found that LPC can mediate follicular development and is a predictor of follicular development ( Yang et al, 2022a ).…”
Section: Discussionmentioning
confidence: 99%
“…One of the metabolites we found to be differentially concentrated in FF from HT patients was a lysophosphatidylcholine, LycoPC(16:0). Lysophosphatidylcholine is secreted by cumulus cells (Gómez-Torres et al ., 2015) and can induce an acrosome reaction in human sperm (Byrd and Wolf, 1986). The acrosome reaction is necessary for sperm to be able to fertilize an oocyte.…”
Section: Discussionmentioning
confidence: 99%